DIFFERENCES OF TUMOR NECROSIS FACTOR EXPRESSION ON VITREOUS WITH AND WITHOUT DIABETIC RETINOPATHY - Suryathi, Ni Made Ari; andayani, ari; andayani, ari (Prosiding Seminar Nasional Sains dan Teknologi (Senastek); Vol 8 No 1 (2023): Senastek 2023, 2023)
Diabetic retinopathy (DR) is a microvascular complication of diabetes mellitus (DM) which can cause visual impairment and even blindness. Tumor Necrosis Factor Alpha (TNF Alpha) is a protein that plays a role in disruption of the Blood Retinal Barrier (BRB) and plays an important role in inflammation and intraocular neovascularization in patients with DR. This study aims to determine differences in TNF Alpha expression in the vitreous of patients with DR and without DR. This study was a cross sectional study by taking vitreous samples from patients with DR and without DR. The number of subjects in this study were 40 type 2 DM patients with 51.2% of DR patients suffering from type 2 DM for more than 10 years. The mean vitreous TNF Alpha level was found to be 5.07 pg/ml (2.07-8.07 pg/ml). There were differences in TNF Alpha levels in the group without DR and the DR group and using the t test a significant difference was found with a mean difference of 99.18 (79.8-118.5); TNF Alpha in the DR group was 52.65 pg/ml and without DR was 8.16 with p < 0.001. Retinal ischemic conditions increase TNF Alpha expression in DR patients.